Running demands and heart rate response in Rugby Sevens referees - Suarez Moreno Arrones, L. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
To date, only very limited information exists on the physiological and running demands associated to match play in rugby refereeing, and no data are available yet on rugby sevens. Accordingly, the aim of this study was to examine for the first time the match running demands and exercise intensity associated with men rugby sevens refereeing. Methods: Time-motion analysis of running activity was collected from 12 elite male rugby referees. Match analyses were performed 2-4 times on each referee during a total of 38 matches played during two international rugby sevens tournaments. Portable global position system (GPS) technology and heart rate (HR) responses were used to assess match running demands and exercise intensity, respectively. GPS data were recorded at 15 Hz frequency. Results: Referees covered an average distance of 1665.2 m per game. Over this distance, 22.3% (371.8 m) was spent standing and walking, 25.9% (431.2 m) jogging, 12.4% (206.5 m) cruising, 23.8% (395.6 m) striding, 8% (133.3 m) high-intensity running, and 7.6% (126.7 m) sprinting. The average maximal distance of sprints, the number of sprints and the mean sprint distance over the game were: 31.3±13.4 m, 5.76±3.6 sprints, and 19.9±7.8 m respectively. The referee`s work-to-rest ratio was 3.5:1, and the average heart rate in the second half was higher (P<0.05) than the heart rate recorded in the first half. Discussion: The referees evaluated in the present study were exposed to a higher running demands than their counterparts refereeing other rugby codes (Kay and Gill, 2003; Martin et al., 2001). Compared with video data collected in rugby league (Kay and Gill, 2003) and union (Martin et al., 2001) referees, the current group of rugby sevens referees covered substantial greater total distance per min (110 m/min) in comparison with ~79 m/min in rugby league and 101 m/min in rugby union. The average heart rate of the referees in this study was slightly lower than the estimated HRmax reported in rugby league referees (Kay and Gill, 2004) and the HRmax obtained in male rugby sevens players (Suarez-Arrones et al., 2011).